MANAJEMEN ANESTESI PADA PASIEN TUMOR TIROID DEXTRA SUSPEK KEGANASAN: SEBUAH LAPORAN KASUS - Salsabila, Indah; Indrawan, Khadafi (Medula, 2025)
Thyroid nodules are excessive growth and structural changes with or without functional changes in one or more parts of the thyroid tissue. The prevalence of thyroid cancer is 4-6% of thyroid nodules ( both of single or multiple nodules). Thyroid cancer is the most common endocrine malignancy with an incidence of 3.1% worldwide. One of the treatments for thyroid cancer is thyroidectomy. Indications for thyroidectomy are thyroid malignancy, obstructive symptoms, retrosternal goiter and Graves' disease unresponsive to medical treatment, recurrent hyperthyroidism, Hashimoto's disease and for cosmetic reasons. Thyroid malignancy poses several difficulties in anesthesia. Airway management in patients who have cancer in the head and neck may experience abnormal changes in the airway anatomy. Therefore, it is necessary to prepare an anesthesia plan as well as appropriate pre-operative, intra- operative and post-operative management so that the operation runs smoothly and safely and reduces morbidity and mortality in patients.